Enhancing Audio Data Transfer Through Optical Wireless Communication Using Laser Modulation Techniques - Sam Robert James; Lambert Dwomoh; Raji Fawaz (Applied Engineering, Innovation, and Technology, 2025)
Exploring the potential of optical wireless communication for short-range audio transmission, this research investigates the design of a portable system leveraging the inherent benefits of light-based propagation, such as low power consumption, license-free operation, and enhanced security. While line-of-sight alignment is a key consideration in laser communication, this research outlines a practical approach to system development. A 650 nm laser diode serves as the carrier for the audio signal. The system architecture, comprising a transmitter and receiver, was initially designed and simulated using Proteus software. Each unit was individually implemented and tested to ensure optimal performance. Subsequent integration of these modules and careful line-of-sight alignment enabled successful audio signal transmission and reception. The audible output at the receiver is visually confirmed by a blinking speaker, demonstrating the feasibility of this optical wireless audio communication system. This work offers valuable insights into the design and implementation considerations for such portable applications.